IMPLEMTASI BIMBINGAN KONSELING DALAM PEMBINAAN AKHLAK PESERTA DIDIK - Darul Hikmi, (UNISAN JURNAL, 2024)
This exploration means to decide the job of educators in further developing understudies at school. This kind of examination is clear subjective utilizing the techniques: 1. Perception, 2. Interview, 3. Documentation. The information acquired was diminished and afterward examined. The consequences of the examination got the job of the educator. The job of direction and guiding educators in fostering understudies' ethics is vital in the instructive setting. In view of the conversation above, it tends to be presumed that: 1. Direction and advising educators have the obligation to go with, guide and give advising to understudies in growing great ethics. 2. Plan and execute moral improvement programs in schools, as well as give answers for issues or clashes connected with ethics. 3. As good examples and good examples for understudies, direction and guiding educators should exhibit acceptable conduct and move understudies to emulate their example. 4. Aside from that, it assists understudies with creating attention to virtues and autonomy in picking activities that are as per the ideal ethics. 5. Joint effort with guardians and the local area is additionally essential for his job, to offer the help and data expected to foster understudies' ethics. Via completing this job really, direction and guiding educators make a significant commitment in framing the personality of understudies who have respectable and mindful ethics in day to day existence.